In Situ Doped Polysilicon (ISDP) Hydrophilic Direct Wafer Bonding for MEMS Applications. (28th June 2021) - Stricher, Romain; Gond-Charton, Paul; Amnache, Amrid; Campos, Jose Francisco Ambia; Frechette, Luc; Drouin, Dominique; Ecoffey, Serge
Abstract : In this paper, Chemical Mechanical Polishing is used to reduce RMS roughness of as-deposited ISDP from 3.2 nm down to 0.18 nm. This surface preparation allows ISDP thin films to be direct bonded to polycrystalline and monocrystalline Si, as well as thermal SiO2 . Mechanically strong bondings are obtained showing surface energies higher than the Si fracture energy of 2250 mJ.m −2 and adherence energy up to more than 6000 mJ.m −2 after annealing at 1100 °C. Infrared images and Scanning Acoustic Microscopy confirm that ISDP can be used to fabricate void-free assemblies after annealing. The hermeticity analysis of cavities sealed by ISDP direct bonding showed maximum leak rate lower than 10 −11 Pa.m 3 s −1 after 18 weeks.